Cosmetic surgery advertising exposure, attitudes toward the surgery and surgeons, and perceptions of the advertisement features. (2nd January 2018) - Park, Sung-Yeon; Allgayer, Sasha
ABSTRACT: Introduction: Empirical research on cosmetic surgery advertisements is scarce, in spite of their increasing visibility and ensuing ethical controversies. In the current study, the effects of cosmetic surgery advertising on perceived benefits, risks, acceptance of cosmetic surgery and attitudes toward cosmetic surgeons were examined. Additionally, audience perceptions about the information utility of 27 common elements of cosmetic surgery advertisements were inquired. Method: A web-based cross-sectional survey was conducted with a convenience sample of 343 college students. Results: Exposure to cosmetic surgery advertisements was positively related to perceived benefits and surgery intention, but not related to perceived risk. Compared with doctors in general, cosmetic surgeons were trusted less, though exposure to cosmetic surgery advertisements improved some perceptions about cosmetic surgeons. Among the 27 elements examined, surgeon's education and training, price, financing options, before-and-after photos of patients, patient testimonials, surgeries/procedures available, risks of surgeries/procedures, hygiene-related practices, medical emergency preparedness, and consultation information were rated as helpful. Rated as not helpful were surgeon's portrait photos, office staff photos, highly attractive model photos, after-only photos of actual patients, and celebrity cosmetic surgery information. There were also differences in the evaluation of the 27 elements based on the level of cosmetic surgery advertising exposure and perceived risk. Conclusions: The findings justify marketing efforts of cosmetic surgeons. At the same time, the evaluation of cosmetic surgery advertising elements revealed many areas of confusion among consumers and thus warrants further research and education.